2016
DOI: 10.1155/2016/5341569
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Variable Properties and Moving Heat Source on Magnetothermoelastic Problem under Fractional Order Thermoelasticity

Abstract: A one-dimensional generalized magnetothermoelastic problem of a thermoelastic rod with finite length is investigated in the context of the fractional order thermoelasticity. The rod with variable properties, which are temperature-dependent, is fixed at both ends and placed in an initial magnetic field, and the rod is subjected to a moving heat source along the axial direction. The governing equations of the problem in the fractional order thermoelasticity are formulated and solved by means of Laplace transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…For linearity and by means of the binomial theorem for fractional powers and the assumption |θ/T 0 | 1, the radial equation of motion (19) and constitutive relations (8) will be in the forms…”
Section: Temperature-dependent Thermal Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…For linearity and by means of the binomial theorem for fractional powers and the assumption |θ/T 0 | 1, the radial equation of motion (19) and constitutive relations (8) will be in the forms…”
Section: Temperature-dependent Thermal Conductivitymentioning
confidence: 99%
“…Singh and Kumar [18] explained the rotation effect on micropolar magneto-thermoelastic body. Xiong and Guo [19] investigated the effect of heat source moving with constant speed, and variable properties of a magneto-thermoelastic medium, under the fractional order theory of thermoelasticity. Kumar et al [20] analyzed the interactions subjected to the effect of rotation and hall current in a magneto-thermoelastic micropolar half-space under the fractional order thermoelasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Sherief and Latief [43] found the application of one dimensional thermoelastic problem using the fractional calculus methodology in a half space. Xiong and Guo [59] investigated fractional order thermoelasticity for a one-dimensional finite length generalized magnetothermoelastic problem of a thermoelastic rod. In [35, 40, 41, 44, 56, 57 and 58], various thermoelastic problems studied which based on the theory of fractional-order thermoelastic model.…”
Section: Introductionmentioning
confidence: 99%
“…However, several experimental and theoretical studies have indicated that thermal conductivity is closely related to temperature change [16][17][18][19][20][21][22]. Xiong and Guo [23] validated the effects of variable temperature-dependent properties on field quantities based on a one-dimensional generalized magnetothermoelastic problem. Wang et al [24] studied generalized thermoelasticity with variable thermal material properties and found that variable thermal material properties significantly affect the thermoelastic behaviors, particularly the magnitude of thermoelastic response.…”
Section: Introductionmentioning
confidence: 99%